2022
DOI: 10.1097/hcr.0000000000000665
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supervised Exercise Training on Atrial Fibrillation

Abstract: The role of exercise for treatment of atrial fibrillation (AF) is unknown. A meta-analysis of randomized controlled trials examining exercise training in participants with AF was performed. Exercise training reduced AF recurrence, improved quality of life, and improved cardiorespiratory fitness. AF burden was reduced in studies that included continuous monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 41 publications
0
4
1
1
Order By: Relevance
“…This review demonstrated that incorporating CR for patients with AF following RFCA either diminished or did not alter the risk of AF recurrence. This finding stands in contrast to prior systematic reviews [ 22 ]. The preceding review reported a reduction in AF recurrence; however, only three studies were included in the meta-analysis that examined AF recurrence.…”
Section: Reviewcontrasting
confidence: 99%
See 1 more Smart Citation
“…This review demonstrated that incorporating CR for patients with AF following RFCA either diminished or did not alter the risk of AF recurrence. This finding stands in contrast to prior systematic reviews [ 22 ]. The preceding review reported a reduction in AF recurrence; however, only three studies were included in the meta-analysis that examined AF recurrence.…”
Section: Reviewcontrasting
confidence: 99%
“…There is no conclusive evidence that moderate-intensity CR increases the incidence of AF, and its role in AF recurrence after RFCA has not been determined. Previously, a systematic review was conducted examining the prevention of AF recurrence with exercise [ 22 ]. However, the results are uncertain because fewer than three studies were included in that review, and exercise intensity was not standardized.…”
Section: Introductionmentioning
confidence: 99%
“…Recommendation-Specific Supportive Text In patients with nonpermanent AF, aerobic exercise training may contribute to a reduction in AF burden and improve maintenance of sinus rhythm. 2–5 Aerobic exercise interventions reduce severity of AF symptoms, increase functional capacity, and improve health-related QOL among patients with both nonpermanent and permanent AF. 1,3,6 Initiation of or continuing regular exercise after development of AF was associated with a lower risk of HF and mortality in a population-based cohort study.…”
Section: Lifestyle and Risk Factor Modification (Lrfm) For Af Managementmentioning
confidence: 99%
“…Randomized studies examining the impact of lifestyle modification and cardiac rehabilitation on secondary prevention of AF have been limited in size and duration, with few evaluating sustainability. 4 , 5 , 8 The ACTIVE-AF trial demonstrated that a tailored aerobic-based exercise program reduced AF symptom severity and improved maintenance of sinus rhythm. 9 These benefits were achieved in the absence of weight loss.…”
Section: Discussionmentioning
confidence: 99%